Impact of widowhood cultural. practices and locus of control on perceived social support of widows in Anambra, Nigeria (2006)
This study examined the impact of widowhood cultural practices on perceived social support of widows. 185 widows purposively drawn from 16 Local Government Area in Anambra State participated in the study, with ages ranging from 26-90 years. Data collection was through the aid of a questionnaire consisting of widowhood cultural practices scale, the locus of control scale and perceived social support scale. Result indicated that widowhood cultural practices have significant effect on the perception of social support of widows; widows who experienced lenient form of widowhood practice have more positive perception of social support than those who experienced harsh form of practice. It was also found that widows with int~rna1 locus of control have more positive perception of social support' than those with external locus of control. The length of widowhood and age of widows were also found to affect perception of social support by widows. Thus, it is suggested that a cultural reorientation that enhances acceptance of widows should be encouraged. This would reduce the prevalence of practices that dehumanize widows and reduce them to psychological wrecks. Also, assertiveness training and other psychological buffers should be made available to boost the self-esteem of widows and make them relatively psychologically independent.